Improvement of Physical Training of Students Through the Means of Pouches Sport (Workout) - Eshonkulov Uktam Rayimkulovich (Genius Journals, 2022)
Organizing the construction of the car plant in the flow method of calendar plan modeling, creating a methodology for developing a calendar plan, identifying technical and economic advantages and applying them in design practice.
Keywords: Walking; running; mini-football; cycling